Diagnosis of osteopenic syndrome. Osteopenic syndrome in bronchial asthma patients - O. P. Zorkaltseva; V. D. Zavadovskaya; O. S. Kobyakova; O. Yu. Kilina; E. Sh. Nigmatova (Бюллетень сибирской медицины)
Osteopenic syndrome in chronic obstructive pulmonary diseases including bronchial asthma represents actual and insufficiently studied area of medical science in view of ambiguous data on influence of glucocorticosteroid therapy and inflammation as basic pathogenetic mechanisms of bronchial asthma on bone metabolism. This review covers issues of pathogenesis and diagnosis of secondary osteopenic syndrome in patients with bronchial asthma.